EMPLOYEE INNOVATIVE WORK BEHAVIOR MEMEDIASI PENGARUH KNOWLEDGE SHARING PADA KINERJA KARYAWAN - Fanani, Fahmi; Wiratama, Dadang (LP2M Universitas Bina Bangsa, 2025)
This study aims to explore the effect of knowledge sharing on employee performance with employee innovative work behavior as a mediating variable. Using the Partial Least Square (PLS) method, data were obtained from 80 employees of KSP Pratama Surya Makmur Lamongan. The results showed that knowledge sharing has a significant effect on employee performance, both directly and through the mediation of innovative work behavior. These results emphasize the importance of creating a knowledge sharing culture that supports innovation to improve organizational productivity and efficiency. Based on the Social Exchange theory, this study provides insight into how knowledge sharing practices can be optimally utilized in organizations.